Multiscale simulation of flow in gas-lubricated journal bearings: A comparative study between the Reynolds equation and lattice Boltzmann methods - Yulong Jiang (Taylor & Francis Group, 2021)
On account of varying tiny cross-sectional clearance and fairly high bearing speed, the feature of lubricant gas of gas-lubricated journal bearings (GLJBs) is a complex multiscale problem. In this research, both macroscopic Reynolds equation and mesoscopic lattice Boltzmann methods (LBM) are adopted to successfully establish models for restoring flow characteristics of GLJBs from continuum, slip to transition flow regimes. The influences of eccentricity ratios, bearing speeds and Knudsen numbers (Kn) on pressure, thickness, velocity distributions and flow fields of lubricant flow are investigated. The distinctions between the results through two methods, which can be complementary, are compared and analyzed with maximum error ≯9.6%. It indicates that keeping the eccentricity ratio or bearing speed at appropriate high levels is good for improving its working performance. When Kn is enhanced, the maximum and minimum pressure peaks will decrease and increase, respectively, whereas, the impact degree of rarefaction effect on the pressure distribution will reduce after Kn exceeding a certain level. Besides, an interesting backflow phenomenon in the lubricant flow field is demonstrated. This investigation enriches numerical models for GLJBs at different flow regimes, and provides new fruitful insights into the flow characteristics at multiscale.